Effects of pre-competitional rapid weight loss on nutrition, vitamin status and oxidative stress in elite boxers - Reljic, Dejan; Jost, Joachim; Dickau, Kirsten; Kinscherf, Ralf; Bonaterra, Gabriel; Friedmann-Bette, Birgit (Journal of Sports Sciences, 2015)
Abstract: Dietary intake, vitamin status and oxidative stress were evaluated in 17 elite male boxers. Ten of them frequently reduced body weight rapidly before competitions (Weight Loss Group) and 7 did not practice rapid weight loss (Control Group). Food record checklists, blood samples for determination of vitamin status and plasma glutathione levels were obtained during a week of weight maintenance, a pre-competition week and a post-competition week. The average dietary intakes in both groups were 33 ± 8 kcal·kg−1, 3.7 ± 1.1 g·kg−1 carbohydrates, 1.5 ± 0.4 g·kg−1 protein, 1.2 ± 0.4 g·kg−1 fat and 2.2 ± 1.0 L water per day (excluding pre-competition week in Weight Loss Group). Energy (18 ± 7 kcal·kg−1), carbohydrate (2.2 ± 0.8 g·kg−1), protein (0.8 ± 0.4 g·kg−1), fat (0.6 ± 0.3 g·kg−1) and water (1.6 ± 0.6 L) consumption (P-values <0.001) and intakes of most vitamins (P-values < 0.05) were significantly reduced during the pre-competition week in the Weight Loss Group. In both groups, the intakes of vitamins A, E and folate were below recommended values throughout the three periods; however, blood vitamin and plasma glutathione levels did not change significantly. Our findings indicate a low-caloric and low-carbohydrate diet in elite boxers, regardless of participating in rapid weight loss or not. Apparently, the pre-competitional malnutitrition in the Weight Loss Group did not induce alterations in the vitamin and glutathione status.
CRIS-Team Scopus Importer:2022-10-11
Keywords: antioxidants; combat sports; energy restriction; nutrient intake